2023
DOI: 10.1021/acs.analchem.2c05046
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Aptamer-Coupled Microelectrode Fiber Sensors (apta-μFS) for Highly Selective Neurochemical Sensing

Abstract: The selective and sensitive sensing of neurochemicals is essential to decipher in-brain chemistry underlying brain pathophysiology. The recent development of flexible and multifunctional polymer-based fibers has been shown useful in recording and modulating neural activities, primarily electrical ones. In this study, we were able to realize fiber-based neurochemical sensing with high sensitivity and selectivity. We achieved a generalizable method to couple aptamers, a type of synthetic receptors on the carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…5c). 88 The study demonstrated the potential of fiber-based toolsets for multimodal exploration of brain pathophysiology, showing how these sensors can provide valuable insights into the neurochemical basis of neurological conditions.…”
Section: Nucleic Acid-based Implantable Sensorsmentioning
confidence: 93%
“…5c). 88 The study demonstrated the potential of fiber-based toolsets for multimodal exploration of brain pathophysiology, showing how these sensors can provide valuable insights into the neurochemical basis of neurological conditions.…”
Section: Nucleic Acid-based Implantable Sensorsmentioning
confidence: 93%
“…Aptamers (Apt) are synthetic single-stranded oligonucleotides with the advantages of easy customization, high stability, and low target binding cross-reactivity. , The defined aptamer sequences enable them to bind to target molecules with high affinity, thereby inducing a reversible three-dimensional conformational change from a relatively simple chain structure to a complex structure wrapped around the target molecules. , Recently, electrochemical aptamer biosensors (E-AB) that integrate the molecular recognition properties of aptamers with high-resolution in vivo electrochemistry have attracted much discussion. Commonly, self-assembly of sulfhydryl groups on gold electrodes enables immobilization of aptamers but is rarely used for in vivo analysis, possibly because nonspecific adsorption of oligonucleotides on the gold surface usually results in poor control of its density and orientation. , Hou et al strategically assembled aptamer cholesterol amphiphiles onto an alkyl chain-functionalized CFE surface via cholesterol-alkyl chain supramolecular interactions, providing an in vivo selective sensing interface. Also, Saizaki et al constructed supramolecular assemblies through π–π stacking interactions between 1-pyrenebutanoic acid succinimidyl ester (PBASE) and carbon nanotubes, which allowed the amino-terminated aptamer to covalently bind to PBASE via an ammonolysis reaction. Despite the impressive achievements of E-AB in highly selective sensing, it remains a challenge to achieve aptamer functionalization by a suitable physicochemical design on inert carbon surfaces.…”
Section: Introductionmentioning
confidence: 99%